F Formulasi Dan Evaluasi Serum Gel Ekstrak Daun Sengkubak (Pycnarrhena Cauliflora Diels) - Rini, Ilma Widya; Budi, Setia; Tumanggor, Agustina Hotma Uli (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Serum has a high concentration but a low viscosity. a facial serum that has a fairly good ability to absorb into the skin, releases the active substance of the serum well and is easy to apply to the face. Sengkubak (Pycnarrhena cauliflora Diels) is a type of plant in the Menispermaceae family which can be found in West Kalimantan. Sengkubak also has good potential to be developed as a source of antioxidant compounds Objectives: Knowing the optimal formulation of sengkubak leaf extract serum gel (Pycnarrhena Cauliflora Diels) and knowing the evaluation of the physical properties of Sengkubak leaf extract serum gel (Pycnarrhena Cauliflora Diels) Method: The study used a quasi-experimental design method with varying concentrations of 1 gram, 1.5 grams and 2 grams of natrosol. Serum gel was evaluated for physical organoleptic, homogeneity, spreadability, dry time, adhesion, pH, and viscosity. Results:  The results of the observations on the viscous liquid organoleptic test and on the homogeneity test of homogeneous preparations. the most optimal spreadability test results were formulation 1, the most optimal drying time was formulation 1. the most optimal adhesion test results were formulation 1, the most optimal ph test results were formula 1, and the most optimal viscosity test were formulation 2. Conclusion:  The most optimal serum gel of sengkubak leaf extract (Pycnarrhena Cauliflora Diels) is formulation 1, with a concentration of 1 gram.